The worst-case scenario survival handbook travel - Piven, Joshua 1971-; Borgenicht, David 1968- (Chronicle Books, 2001)
"Presents advice from experts on the techniques they would use to respond to a variety of emergency situations such as delivering a baby in a taxi, fending off a shark, landing an airplane, and others."